Alterations in Sulfur Amino Acid Metabolism in Mice Treated with Silymarin: A Novel Mechanism of Its Action Involved in Enhancement of the Antioxidant Defense in Liver - Kwon, Do Young; Jung, Young Suk; Kim, Sun Ju; Kim, Young Soon; Choi, Dal Woong; Kim, Young Chul (Planta Medica, 2013)
It has been known that silymarin exhibits protective activity against oxidative liver injury induced by various hepatotoxicants, but the underlying mechanism of its beneficial action remains unclear. We determined the alterations in sulfur-containing amino acid metabolism induced by silymarin in association with its effects on the antioxidant capacity of liver. Male mice were treated with silymarin (100 or 200 mg/kg, p. o.) every 12 h for a total of 3 doses, and sacrificed 6 h after the final dosing. The hepatic methionine level was increased, but the activity and protein expression of methionine adenosyltransferase were decreased by silymarin in a dose-dependent manner. S-Adenosylmethionine or homocysteine concentration was not changed, whereas the sulfur-containing metabolites generated from homocysteine in the transsulfuration pathway including cystathionine, cysteine, and glutathione were increased significantly. Cystathionine β-synthase was induced, but cysteine dioxygenase was downregulated, both of which would contribute to the elevation of cysteine and its product, glutathione, in liver. Oxygen radical scavenging capacity of liver cytosol against peroxyl radical and peroxynitrite was increased, and also hepatic lipid peroxidation was diminished in the silymarin-treated mice. Taken together, the results demonstrate that silymarin enhances hepatic glutathione generation by elevating cysteine availability via an increment in cysteine synthesis and an inhibition of its catabolism to taurine, which may subsequently contribute to the antioxidant defense of liver.
Keywords: Silybum marianum; Asteraceae; silymarin; glutathione; sulfur amino acid metabolism; antioxidant